Local cues and asymmetric cell divisions underpin body plan transitions in the moss Physcomitrella patens. - Harrison, C; Roeder, A; Meyerowitz, E; Langdale, J (2009)
BACKGROUND: Land plants evolved from aquatic algae more than 450 million years ago. Algal sisters of land plants grow through the activity of apical initial cells that cleave either in one plane to generate filaments or in two planes to generate mats. Acquisition of the capacity for cell cleavage in three planes facilitated the formation of upright bushy body plans and enabled the invasion of land. Evolutionary transitions between filamentous, planar, and bushy growth are mimicked within moss life cycles. RESULTS: We have developed lineage analysis techniques to assess how transitions between growth forms occur in the moss Physcomitrella patens. We show that initial cells giving rise either to new filaments or bushy shoots are frequently juxtaposed on a single parent filament, suggesting a role for short-range cues in specifying differences in cell fate. Shoot initials cleave four times to establish a tetrahedral shape and subsequently cleave in three planes, generating bushy growth. Asymmetric and self-replacing divisions from the tetrahedral initial generate leaf initials that divide asymmetrically to self-replace and to produce daughter cells with restricted fate. The cessation of division in the leaf is distributed unevenly and contributes to final leaf shape. CONCLUSIONS: In contrast to flowering plants, changes in body plan in P. patens are regulated by cues acting at the level of single cells and are mediated through asymmetric divisions. Genetic mechanisms regulating shoot and leaf development in P. patens are therefore likely to differ substantially from mechanisms operating in plants with more recent evolutionary origins.